The first teachers and students of SENAC – Serviço Nacional de Aprendizagem Comercial of the State of São Paulo: 1946 to 1961 (Research, Society and Development, 2020)
On January 10, 1946, the Serviço Nacional de Aprendizagem Comercial (SENAC) was created nationwide through Decree-Law no. 8,621. The creation of this institution occurred with the combination of numerous factors that indicated the need for a commercial professional school that was aimed at employees of commercial establishments. With 12 articles / objectives, the decree provides for and guides the creation of SENAC, assigning the newly created National Trade Confederation (September 1945) the responsibility of administering and organizing commercial learning schools in the country. In the same year, it started its activities of hiring teachers organized by the Teaching Division, the department responsible for hiring and pedagogical training of teachers and enrollment of students. This article aims to present how the selection process of the first teachers took place, profile, characteristics of the hired teachers and how the pedagogical orientation that aimed at the didactic training of teachers took place. We will also present how the first enrollments and the work carried out by the institution with entrepreneurs and families to publicize the courses took place. Through the primary sources will be presented the profile of the students, the first trainees and the problem of dropout based on a study carried out by Senac / SP, coordinated by the Department of Education Division which aimed to understand the reasons for dropout. For the production of this article, we used primary sources that were located, gathered, selected and analyzed. The main source was the Annual Reports of Senac / SP, produced by the Regional Directorate from the reports sent by the directors of the schools of the State Senac.